Aluminum plastic film, preparation method thereof and soft package secondary battery
By coating the anti-corrosion layer composed of chromium nitrate, acrylic resin and phosphoric acid on the surface of the aluminum foil, the problem of insufficient short-circuit resistance of aluminum-plastic film during short-circuit is solved, the sealing and insulation performance of aluminum-plastic film is improved, and the risk of liquid leakage and corrosion of the battery is reduced.
Patent Information
- Application Number
- CN202510601654.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-09
- Publication Date
- 2025-08-12
AI Technical Summary
The existing aluminum-plastic films have insufficient sealing and insulation properties during the packaging process, resulting in the risk of battery leakage or electrochemical corrosion, and cannot withstand high short-circuit current without being damaged during short-circuit.
The surface of a specific design of aluminum foil is coated with an anticorrosion layer composed of chromium nitrate, acrylic resin and phosphoric acid. By forming a dense complex and hydrogen bonding on the surface of the aluminum foil, the ohmic internal resistance is reduced, the resistance to short circuit of the aluminum foil is improved, and the binding force of the adhesive layer is increased in the aluminum-plastic film.
It realizes that the aluminum-plastic film can withstand high short-circuit current without being damaged when short-circuited, while maintaining good sealing and insulation performance, reducing the risk of liquid leakage and electrochemical corrosion of the battery.
Smart Images

Figure CN120473614A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of production and assembly technology of secondary batteries, in particular to a material production process for secondary batteries, and more particularly to an aluminum-plastic film for secondary batteries and a preparation method thereof. Background Art
[0002] Soft-pack secondary batteries, with their high energy density, fast charging, flexible design, and environmental friendliness, are widely used in new energy industries such as e-cigarettes, mobile phones, laptops, and automobiles. Generally, a soft-pack secondary battery uses a lithium salt as the positive electrode and aluminum-plastic film as the outer packaging material.
[0003] Aluminum plastic film is used as the outer packaging material of soft pack secondary batteries, which usually includes PA / DL1 / AC1 / Al / The AC2 / DL2 / CPP multilayer structure is stacked sequentially. PA (nylon) is the outermost layer, protecting the aluminum foil, providing scratch resistance, and enhancing punching performance. Al (aluminum foil) is the core layer, shielding it from reactive gases such as water and oxygen, and serving as a supporting framework after deep-drawing. CPP (cast polypropylene) is the innermost layer, primarily providing heat sealing and insulation, as well as preventing contact between the electrolyte and the aluminum foil. DL1 is the outer adhesive layer, bonding the PA to the Al. DL2 is the inner adhesive layer, bonding the Al to the CPP. AC1 is a matte anti-corrosion layer for the aluminum foil, providing anchor points between the foil and the outer adhesive layer, thereby improving the bond strength between the PA and Al and high-temperature resistance. AC2 is a glossy anti-corrosion layer for the aluminum foil, enhancing its resistance to electrolyte corrosion and the bond strength between the Al and CPP. Additionally, an SC1 layer can be added to the outer surface of the PA to enhance its slipperiness. Of course, an SC2 layer can also be provided on the outside of the CPP. The SC2 layer is a slippery layer on the CPP surface, used to increase the slipperiness of the CPP, thus forming a multilayer structure of SC1 / PA / DL1 / AC1 / Al / AC2 / DL2 / CPP / SC2.
[0004] A soft-pack secondary battery with an aluminum-plastic film as the outer packaging material generally includes a packaging bag and a battery cell accommodated in the packaging bag. The battery cell includes a core body and a metal terminal, which is electrically connected to the core body and protrudes from the core body. During assembly, the metal terminal portion connected to the core body is extended out of the packaging bag, and the area where the metal terminal and the aluminum-plastic film are in contact is heat-sealed. Specifically, tab glue is placed on both sides of the metal terminal and the area in contact with the aluminum-plastic film. The tab glue is mainly made of CPP. Under a certain temperature and pressure, the end of the aluminum-plastic film extending from the metal terminal is sealed, so that the CPP layer of the aluminum-plastic film and the CPP layer on the tab glue are heat-melted and fused together to achieve a sealing and insulation process. That is, the contact between the metal terminal and the aluminum-plastic film and the sealing of the aluminum-plastic film are achieved by heat-melting the two CPP materials.
[0005] Metal terminals are made of materials including Al, Ni, and Cu, typically with thicknesses ranging from 0.06 to 0.30 mm and widths from 1.5 to 50.0 mm. To improve the battery's current handling capacity, manufacturers may increase the thickness and width of the metal terminals. However, the thicker and wider the metal terminals, the more difficult it is to achieve a top seal. Furthermore, the aluminum-plastic film requires not only a top seal on the protruding end of the metal terminal but also side seals on the other ends that do not extend beyond the metal. Whether sealing the top or side seals on one end, the quality of the seal is crucial. Currently, soft-pack secondary battery manufacturers often use the CPP retention rate to measure seal quality. If the CPP retention rate is too high, the sealing performance is weakened, posing a risk of battery leakage. If the CPP retention rate is too low, the insulation is weakened, leading to the risk of electrochemical corrosion. Both leakage and electrochemical corrosion ultimately shorten the battery's lifespan and compromise safe use. However, both aluminum-plastic film manufacturers and battery manufacturers usually focus on the CPP retention rate of aluminum-plastic film. They know little about the interlayer characteristics of the aluminum-plastic film raw materials, and are not familiar with the details of how to match the later use of the battery end. They are unable to provide aluminum-plastic film that meets the later use of soft-pack batteries and has high comprehensive performance. Summary of the Invention
[0006] Based on the above problems, the present invention provides an aluminum-plastic film, a preparation method thereof, and a soft-pack secondary battery. The aluminum-plastic film not only has excellent sealing performance, but also has high short-circuit resistance. When used as a packaging bag for a soft-pack battery, it can withstand high short-circuit current without being damaged even if a short circuit is caused by contact between a metal terminal and the aluminum foil in the aluminum-plastic film, or by contact between the aluminum foil in the aluminum-plastic film and an external metal part.
[0007] To achieve the above-mentioned objectives, the first aspect of the present invention provides an aluminum-plastic film, comprising a PA layer, a first adhesive layer, a first anti-corrosion layer, an aluminum foil, a second anti-corrosion layer, a second adhesive layer and a CPP layer stacked in sequence, the ohmic internal resistance of the raw material of the aluminum foil is Ω1, the ohmic internal resistance of the aluminum foil after stacking the first anti-corrosion layer and the second anti-corrosion layer is Ω2, the ohmic internal resistance of the aluminum foil after stacking the first adhesive layer and the second adhesive layer is Ω3, Ω1 / Ω2 is 5~10, Ω3 is ≥9000MΩ, and the materials of the first anti-corrosion layer and the second anti-corrosion layer include chromium nitrate, acrylic resin and phosphoric acid.
[0008] The present invention is based on a conventional aluminum-plastic film structure comprising a PA layer, a first adhesive layer, a first anti-corrosion layer, an aluminum foil, a second anti-corrosion layer, a second adhesive layer and a CPP layer stacked in sequence. By specially designing the materials of the first anti-corrosion layer and the second anti-corrosion layer, the ohmic internal resistance of the aluminum foil after the first anti-corrosion layer and the second anti-corrosion layer are stacked is greatly reduced, with Ω1 / Ω2 being 5-10. Therefore, the aluminum-plastic film not only has the better sealing and insulation properties of a conventional structure, but also has higher short-circuit resistance. Even if a short circuit is caused by contact between a metal terminal and the aluminum foil in the aluminum-plastic film, or by contact between the aluminum foil in the aluminum-plastic film and an external metal component, the aluminum-plastic film can withstand a higher short-circuit current without being damaged. Specifically, the materials of the first anti-corrosion layer and the second anti-corrosion layer include chromium nitrate, acrylic resin and phosphoric acid. In a phosphoric acid environment, chromium nitrate will react on the surface of the aluminum foil to form complexes such as chromate and phosphate, and acrylic resin will penetrate into the pores of the porous oxide layer of the aluminum layer. Through solidification, a dense filling layer is formed, which reduces the contact of the aluminum layer with the external environment and improves the corrosion resistance. At the same time, the polar groups in the acrylate form hydrogen bonds with the -OH on the surface of the aluminum layer, increasing the bonding force with the aluminum layer. At the same time, it has good conductive properties, which can greatly reduce the ohmic internal resistance of the aluminum foil. Therefore, it can withstand large currents without damage when a short circuit occurs.
[0009] As a technical solution of the present invention, Ω1 is 30-40 MΩ, and Ω2 is ≤5 MΩ.
[0010] As a technical solution of the present invention, the mass ratio of the chromium nitrate, the acrylic resin and the phosphoric acid is 100:40~60:1~10.
[0011] As a technical solution of the present invention, the chromium nitrate is Cr(NO3)3.9H2O, the acrylic resin is a water-based acrylic resin, the number average molecular weight of the acrylic resin is 20,000-40,000, and the phosphoric acid is analytically pure H3PO4.
[0012] As a technical solution of the present invention, the adhesive in the first adhesive layer is a polyurethane adhesive and the dry adhesive amount is 4.0-5.0 g / m2 The adhesive in the second adhesive layer is a modified polyolefin adhesive and the dry adhesive amount is 2.2~2.8g / m 2 .
[0013] As a technical solution of the present invention, the polyurethane adhesive includes at least one of polyether polyurethane, polyester polyurethane, aromatic polyurethane and aliphatic polyurethane, and the modified polyolefin adhesive includes at least one of maleic anhydride modified polyolefin and acrylic acid modified polyolefin.
[0014] As a technical solution of the present invention, the raw material of the aluminum foil has an Al content ≥99.2wt.%, an Fe content ≤0.3wt.%, a Si content ≤0.15wt.%, a Cu content ≤0.055wt.%, a Mn content ≤0.05wt.%, and a Zn content ≤0.1wt.%.
[0015] A second aspect of the present invention provides a method for preparing an aluminum-plastic film, comprising the steps of: (1) coating the anti-corrosion liquid corresponding to the first anti-corrosion layer and the second anti-corrosion layer on both sides of the aluminum foil respectively, and then drying; (2) coating the first adhesive liquid corresponding to the first adhesive layer on the first anti-corrosion layer and coating the second adhesive liquid corresponding to the second adhesive layer on the second anti-corrosion layer; (3) A PA layer is laminated on the first adhesive liquid and a CPP layer is laminated on the second adhesive liquid, and then aged.
[0016] The preparation method prepares an aluminum-plastic film composed of a PA layer, a first adhesive layer, a first anti-corrosion layer, an aluminum foil, a second anti-corrosion layer, a second adhesive layer and a CPP layer stacked in sequence through the coating and drying of an anti-corrosion liquid, the coating of an adhesive liquid, the lamination of a PA layer and the lamination of a CPP layer. The preparation method is simple to operate and has a high degree of industrial feasibility.
[0017] A third aspect of the present invention provides a soft-pack secondary battery, comprising a packaging bag and a battery cell accommodated in the packaging bag, wherein the battery cell comprises a core body and a metal terminal, wherein the metal terminal is connected to the core body and protrudes from the core body, and the packaging bag is the aforementioned aluminum-plastic film or an aluminum-plastic film prepared by the aforementioned aluminum-plastic film preparation method, and the metal terminal comprises a connecting portion, a contact portion and an extending portion connected in sequence, wherein the connecting portion is connected to the core body, the contact portion contacts the aluminum-plastic film, and the extending portion extends out of the packaging bag.
[0018] The soft-pack secondary battery has a high-performance aluminum-plastic film with a CPP retention rate of 50-80%. The strength of the area where the aluminum-plastic film contacts the contact part is ≥2N / 6mm, and the strength of the area where the aluminum-plastic film does not contact the contact part is ≥55N / 15mm. The bursting pressure of the aluminum-plastic film is ≥1.0Mpa, and the shell resistance of the aluminum-plastic film is ≥200MΩ. Therefore, the soft-pack secondary battery is not only easy to seal, but also has no risk of leakage and electrochemical corrosion, is not easy to explode, has high insulation, and can withstand high short-circuit current without being damaged when encountering a short-circuit risk. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a partial perspective schematic diagram of the soft-pack secondary battery of the present invention.
[0020] Figure 2 This is a cross-sectional morphology image of the area where the aluminum-plastic film contacts the contact portion of the soft-pack secondary battery using the aluminum-plastic film of Example 1 of the present invention.
[0021] Figure 3 This is a cross-sectional morphology image of the area where the aluminum-plastic film contacts the contact portion of the soft-pack secondary battery using the aluminum-plastic film of Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0022] The inventors of the present invention have greatly improved the short-circuit resistance of the aluminum-plastic film by specifically selecting the materials of the first anti-corrosion layer and the second anti-corrosion layer on the basis of the conventional aluminum-plastic film structure comprising a PA layer, a first adhesive layer, a first anti-corrosion layer, an aluminum foil, a second anti-corrosion layer, a second adhesive layer and a CPP layer stacked in sequence. This allows the aluminum-plastic film to withstand a higher short-circuit current without being damaged when encountering a short-circuit risk when used as a packaging bag. Therefore, while maintaining the sealing and insulation properties of the conventional aluminum-plastic film multi-layer structure, the inventors have also explored the problems encountered in the later use of the aluminum-plastic film when matching the battery terminal, thereby meeting the higher comprehensive performance requirements of the soft-pack battery in the later use.
[0023] The improved aluminum-plastic film of the present invention includes a PA layer, a first adhesive layer, a first anticorrosion layer, an aluminum foil, a second anticorrosion layer, a second adhesive layer, and a CPP layer stacked in sequence. The improved aluminum-plastic film can have a thickness of 105 to 125 μm, the aluminum foil can have a thickness of 35 to 55 μm, the PA layer can have a thickness of 15 to 28 μm, and the CPP layer can have a thickness of 30 to 50 μm.
[0024] The raw materials of the aluminum foil have an Al content of ≥99.2 wt.%, an Fe content of ≤0.3 wt.%, a Si content of ≤0.15 wt.%, a Cu content of ≤0.055 wt.%, a Mn content of ≤0.05 wt.%, and a Zn content of ≤0.1 wt.%. The raw materials of the aluminum foil are prepared by metal alloying to have an ohmic internal resistance Ω1 of 30 to 40 MΩ. The ohmic internal resistance Ω1 can be any value between 30 and 40 MΩ. For example, Ω1 can be, but is not limited to, 30 MΩ, 31 MΩ, 32 MΩ, 33 MΩ, 34 MΩ, 35 MΩ, 36 MΩ, 37 MΩ, 38 MΩ, 39 MΩ, or 40 MΩ.
[0025] The first and second anti-corrosion layers are identical and made of chromium nitrate, acrylic resin, and phosphoric acid. The mass ratio of chromium nitrate, acrylic resin, and phosphoric acid is 100:40-60:1-10. For example, the mass ratio may be, but is not limited to, 100:40:1, 100:45:1, 100:50:1, 100:55:1, 100:60:1, 100:40:5, 100:45:5, 100:50:5, 100:55:5, 100:60:5, 100:40:10, 100:45:10, 100:50:10, 100:55:10, and 100:60:10. The chromium nitrate is Cr(NO3)3.9H2O, the acrylic resin is a water-based acrylic resin, the number average molecular weight of the acrylic resin is 20,000-40,000, the phosphoric acid is analytically pure H3PO4, and the ohmic internal resistance of the aluminum foil after laminating the first and second anti-corrosion layers is Ω2, where Ω2 is ≤5 MΩ, and Ω1 / Ω2 is 5-10. Ω2 can be any value ≤5 MΩ, and for example, can be, but not limited to, 1 MΩ, 2 MΩ, 3 MΩ, 4 MΩ, or 5 MΩ. Ω1 / Ω2 can be any value between 5 and 10, and for example, can be, but not limited to, 5, 6, 7, 8, 9, or 10. The ohmic resistance of aluminum foil decreases because chromium nitrate reacts on the surface of the aluminum foil in a phosphoric acid environment to form complexes such as chromate and phosphate, which then combine with the polar groups in the acrylate to form hydrogen bonds with the -OH on the surface of the aluminum layer, increasing the bonding strength with the aluminum layer. At the same time, it has good conductive properties, which can greatly reduce the ohmic internal resistance of the aluminum foil.
[0026] The adhesive in the first adhesive layer is a polyurethane adhesive and the dry adhesive weight is 4.0~5.0g / m 2 As an example, the dry glue amount can be but not limited to 4.0g / m 2 , 4.1g / m 2 , 4.2g / m 2 , 4.3g / m 2 , 4.4g / m 2 4.5g / m 2 , 4.6g / m2 , 4.7g / m 2 , 4.8g / m 2 , 4.9g / m 2 , 5.0g / m 2 The polyurethane adhesive includes at least one of polyether polyurethane, polyester polyurethane, aromatic polyurethane and aliphatic polyurethane. The adhesive in the second adhesive layer is a modified polyolefin adhesive and the dry adhesive amount is 2.2~2.8g / m 2 As an example, the dry glue amount can be but not limited to 2.2g / m 2 , 2.3g / m 2 , 2.4g / m 2 , 2.5g / m 2 , 2.6g / m 2 , 2.7g / m 2 , 2.8g / m 2 The modified polyolefin adhesive includes at least one of maleic anhydride-modified polyolefin and acrylic acid-modified polyolefin. After laminating the first and second adhesive layers, the aluminum foil exhibits an ohmic internal resistance of Ω3, with Ω3 ≥ 9000 MΩ, and can further be 9999.99 MΩ, indicating that the aluminum foil is now completely insulated by the anti-corrosion layer and the anti-corrosion layer.
[0027] In addition, a slippery layer may be provided on the PA and CPP layers to enhance the slipperiness of the PA and CPP layers. The slippery layer may be conventionally provided. For example, the slippery layer on the PA layer may be made of one or more of erucamide and stearamide, and the slippery layer on the CPP layer may be made of one or more of erucamide and stearamide. The method for preparing the aluminum-plastic film of the present invention may include the following steps.
[0028] (1) Coat the anti-corrosion liquid corresponding to the first anti-corrosion layer and the second anti-corrosion layer on both sides of the aluminum foil respectively, and then dry.
[0029] (2) Coating a first adhesive liquid corresponding to the first adhesive layer on the first anti-corrosion layer and coating a second adhesive liquid corresponding to the second adhesive layer on the second anti-corrosion layer.
[0030] (3) A PA layer is laminated on the first adhesive and a CPP layer is laminated on the second adhesive, and then aged.
[0031] The coating in the preparation method of the aluminum-plastic film of the present invention can be performed using conventional methods, such as spraying, brushing, and extrusion coating. The drying temperature can be 60-110°C, and the drying time can be 10-20 seconds. As an example, the temperature can be, but is not limited to, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, and 110°C. The aging temperature can be 55-80°C. As an example, the temperature can be, but is not limited to, 55°C, 60°C, 65°C, 70°C, 75°C, and 80°C. The aging time is 2-8 days. As an example, the time can be, but is not limited to, 2 days, 3 days, 4 days, 5 days, 6 days, 7 days, and 8 days. The first and second adhesives can be polyurethane adhesives or modified polyolefin adhesives diluted with conventional organic solvents to facilitate coating.
[0032] The aluminum-plastic film of the present invention can be used as a packaging bag in a soft-pack battery. As a soft-pack secondary battery using the aluminum-plastic film of the present invention, Figure 1 As shown, the soft-pack secondary battery 100 includes a packaging bag 10 and a battery cell 30 housed therein. The battery cell 30 includes a core body 31 and a metal terminal 33. The metal terminal 33 is electrically connected to the core body and protrudes from the core body 31. The metal terminal 33 includes a positive terminal 33a and a negative terminal 33b. The thickness of the metal terminal 33 can be 80-130 μm and the width can be 3-10 mm. The metal terminal 33 includes a connecting portion 331, a contact portion 333, and an extension portion 335, which are connected in sequence. The connecting portion 331 connects to the core body 31, the contact portion 333 contacts the packaging bag 10, and the extension portion 335 extends out of the packaging bag 10. The packaging bag 10 is made of the aluminum-plastic film of the present invention. After punching a hole, the battery cell is placed in the hole. The aluminum-plastic film is folded in half and then sealed at the top and sides. The top seal forms a top seal edge 11, and the side seals form a first side seal edge 13 and a second side seal edge 15. The side seal can be performed using a heat sealer. During the top seal, tab glue 35 is placed on both sides of the metal terminal 33 in the area where the aluminum-plastic film contacts. The thickness of the tab glue 35 can be 65-100 μm and the width can be 1-5 mm. The tab glue 35 is mainly made of CPP. Under a certain temperature and pressure, the top seal is performed on the end of the aluminum-plastic film extending from the metal terminal 33, causing the CPP layer of the aluminum-plastic film to fuse together with the CPP layer on the tab glue, thereby achieving sealing and insulation. In other words, the contact between the metal terminal and the aluminum-plastic film and the sealing of the aluminum-plastic film are achieved by the heat fusion of the two CPP materials.
[0033] The CPP retention rate of the aluminum-plastic film in the soft-pack secondary battery of the present invention is 50-80%. As an example, the CPP retention rate can be, but is not limited to, 50%, 55%, 60%, 65%, 70%, 75%, or 80%.
[0034] CPP retention rate = (1 - uncompressed thickness / initial total thickness) × 100%. For packages without metal terminals, the initial total thickness is the total thickness of the aluminum-plastic film, and the uncompressed thickness is the thickness of the nylon, aluminum layer, and remaining CPP after heat sealing. For packages with metal terminals, the initial total thickness is the total thickness of the aluminum-plastic film + the total thickness of the metal terminals, and the uncompressed thickness is the thickness of the nylon, aluminum layer, metal terminals, and remaining CPP after heat sealing. The specific calculation formula is as follows.
[0035] The calculation formula for the CPP retention rate of the aluminum-plastic film in the heat-sealed area of the metal terminal is as follows.
[0036] Tab CPP retention rate = 1-(initial thickness of aluminum-plastic film × 2 + initial total thickness of tab - tab seal thickness) / (initial CPP thickness of aluminum-plastic film × 2 + initial total thickness of tab - metal strip thickness) × 100% The calculation formula for the CPP retention rate of aluminum-plastic film in the heat-sealed area where no metal terminal exists is as follows.
[0037] The CPP retention rate of the heat-sealed area of the non-metallic terminal is = (1-the thickness of the lost CPP / the initial thickness of the two layers of CPP) × 100% The aluminum-plastic film in the soft-pack secondary battery of the present invention is observed by end-face slicing. The morphology of the sealed slices of the side seals is not cracked or raised and is in the shape of an arc. The morphology of the slices of the top seal area where the metal terminals are present is free of holes and the metal terminals are not in contact with the aluminum foil in the aluminum-plastic film. The morphology of the sealed slices of the side seals and the morphology of the slices of the top seal area where the metal terminals are present refer to the cutting of the specimens along the direction of the metal terminals (if it is a sealed slice of the side seals, it is sampled perpendicular to the side seal direction). During the slicing morphology operation, the unpackaged aluminum-plastic film reserved area is 3 mm long, and then a REM-710 slicer is used to pre-treat the slices perpendicular to the sealing direction. The end faces of the slices are smooth and free of burrs. A Keyence microscope is used to observe the end faces of the pre-treated samples at 1000X, and the morphology after the fusion of the CPP layer in the aluminum-plastic film and the CPP layer in the tab glue can be observed. Insufficient sol filling is called poor fusion, which can lead to leakage risk in the battery. The smaller the gap between the sharp corners of the metal terminal and the aluminum foil in the aluminum-plastic film, the greater the risk of electrochemical corrosion. If the side seal has an arc-shaped morphology without cracks or bulges, it is considered a standard morphology.
[0038] After packaging, the soft-pack secondary battery of the present invention is torn open, and the sol in the sealed area is uniformly milky white. During operation, apply force as evenly as possible to the sealed area along the sealing direction, tear open the sealed edge, and observe whether the sol in the sealed area is uniformly milky white.
[0039] The strength (I1) of the area where the aluminum-plastic film of the soft-pack secondary battery of the present invention contacts the contact portion of the metal terminal is ≥2N / 6mm, and the strength (I2) of the area where the aluminum-plastic film does not contact the contact portion is ≥55N / 15mm. During testing, the seal of the top seal area is cut along the length of the metal terminal, leaving a 15mm long area of the unsealed aluminum-plastic film. The test is performed using a universal tensile testing machine with a sensor range of 100N. The clamps of the universal tensile testing machine are respectively clamped to the unsealed aluminum-plastic film reserved area, with a clamp spacing of 50mm and a speed of 300mm / min. The average of the maximum and minimum force values is taken as the strength of the aluminum-plastic film in the area in contact with the contact portion of the metal terminal. The sampling direction is adjusted to be perpendicular to the sealing direction of the top seal, and the sampling width is 15mm. The strength of the area where the aluminum-plastic film does not contact the contact portion can be obtained using the same method.
[0040] The explosion pressure of the aluminum-plastic film in the soft-pack secondary battery of the present invention is ≥1.0 MPa. During the test, a micro needle with a pressure gauge is passed through the bottom of the soft-pack secondary battery to introduce nitrogen. The value of the pressure gauge when the battery explodes is recorded, which is the explosion pressure.
[0041] The shell resistance of the aluminum-plastic film in the soft-pack secondary battery of the present invention is ≥200 MΩ. During the test, a 6.5-digit tester is used, with the red electrode contacting the negative terminal of the battery, and the black electrode piercing the aluminum-plastic film at the top edge seal and contacting the aluminum foil in the aluminum-plastic film. The load is 200 V, and the contact time is 2.5 seconds. The recorded resistance value is the shell resistance, which represents the insulation property of the CPP retention rate in the metal terminal area.
[0042] In order to better illustrate the purpose, technical solutions and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.
[0043] Example 1 This embodiment is an aluminum-plastic film including a PA layer, a first adhesive layer, a first anti-corrosion layer, an aluminum foil, a second anti-corrosion layer, a second adhesive layer and a CPP layer stacked in sequence. The raw material of the aluminum foil has an Al content of 99.5wt.%, a Fe content of 0.2wt.%, a Si content of 0.1wt.%, a Cu content of 0.05wt.%, a Mn content of 0.05wt.%, and a Zn content of 0.1wt.%. The materials of the first anti-corrosion layer and the second anti-corrosion layer include Cr(NO3)3.9H2O, acrylic resin and phosphoric acid in a mass ratio of 100:50:5, and the acrylic resin is a water-based acrylic resin with a number average molecular weight of 30,000. The adhesive in the first adhesive layer is an aromatic polyurethane adhesive and the dry adhesive amount is 4.5g / m 2The adhesive in the second adhesive layer is a maleic anhydride modified polyolefin resin, and the dry adhesive weight is 2.6g / m 2 .
[0044] The method for preparing the aluminum-plastic film of this embodiment may include the following steps.
[0045] (1) Coat the anti-corrosion liquid corresponding to the first anti-corrosion layer and the second anti-corrosion layer on both sides of the aluminum foil, and then dry at 100°C for 3 hours.
[0046] (2) Coating a first adhesive liquid corresponding to the first adhesive layer on the first anti-corrosion layer and coating a second adhesive liquid corresponding to the second adhesive layer on the second anti-corrosion layer.
[0047] (3) A PA layer was laminated on the first adhesive and a CPP layer was laminated on the second adhesive, and then aged at 70°C for 5 days.
[0048] Example 2 This embodiment is an aluminum-plastic film including a PA layer, a first adhesive layer, a first anti-corrosion layer, an aluminum foil, a second anti-corrosion layer, a second adhesive layer and a CPP layer stacked in sequence. The raw material of the aluminum foil has an Al content of 99.4wt.%, a Fe content of 0.30wt.%, a Si content of 0.15wt.%, a Cu content of 0.03wt.%, a Mn content of 0.04wt.%, and a Zn content of 0.08wt.%. The materials of the first anti-corrosion layer and the second anti-corrosion layer include Cr(NO3)3.9H2O, acrylic resin and phosphoric acid in a mass ratio of 100:55:8, and the acrylic resin is a water-based acrylic resin with a number average molecular weight of 35,000. The adhesive in the first adhesive layer is a polyester polyurethane adhesive and the dry adhesive amount is 4.8g / m 2 The adhesive in the second adhesive layer is acrylic modified polyolefin resin, and the dry adhesive weight is 2.5g / m 2 .
[0049] The method for preparing the aluminum-plastic film of this embodiment may include the following steps.
[0050] (1) Coat the anti-corrosion liquid corresponding to the first anti-corrosion layer and the second anti-corrosion layer on both sides of the aluminum foil, and then dry at 80°C for 5 hours.
[0051] (2) Coating a first adhesive liquid corresponding to the first adhesive layer on the first anti-corrosion layer and coating a second adhesive liquid corresponding to the second adhesive layer on the second anti-corrosion layer.
[0052] (3) A PA layer was laminated on the first adhesive and a CPP layer was laminated on the second adhesive, and then aged at 75°C for 7 days.
[0053] Comparative Example 1 This comparative example is an aluminum-plastic film including a PA layer, a first adhesive layer, a first anti-corrosion layer, an aluminum foil, a second anti-corrosion layer, a second adhesive layer and a CPP layer stacked in sequence. The raw materials of the aluminum foil have an Al content of 99.5wt.%, a Fe content of 0.2wt.%, a Si content of 0.1wt.%, a Cu content of 0.05wt.%, a Mn content of 0.05wt.%, and a Zn content of 0.1wt.%. The materials of the first anti-corrosion layer and the second anti-corrosion layer include Cr(NO3)3.9H2O and acrylic resin in a mass ratio of 100:50, and the acrylic resin is a water-based acrylic resin with a number average molecular weight of 30,000. The adhesive in the first adhesive layer is an aromatic polyurethane adhesive and the dry adhesive amount is 4.5g / m 2 The adhesive in the second adhesive layer is a maleic anhydride modified polyolefin resin, and the dry adhesive weight is 2.6g / m 2 .
[0054] The preparation method of the aluminum-plastic film of this comparative example may include the following steps.
[0055] (1) Coat the anti-corrosion liquid corresponding to the first anti-corrosion layer and the second anti-corrosion layer on both sides of the aluminum foil, and then dry at 100°C for 3 hours.
[0056] (2) Coating a first adhesive liquid corresponding to the first adhesive layer on the first anti-corrosion layer and coating a second adhesive liquid corresponding to the second adhesive layer on the second anti-corrosion layer.
[0057] (3) A PA layer was laminated on the first adhesive and a CPP layer was laminated on the second adhesive, and then aged at 70°C for 5 days.
[0058] Comparative Example 2 This comparative example is an aluminum-plastic film including a PA layer, a first adhesive layer, a first anti-corrosion layer, an aluminum foil, a second anti-corrosion layer, a second adhesive layer and a CPP layer stacked in sequence. The raw materials of the aluminum foil have an Al content of 99.5wt.%, a Fe content of 0.2wt.%, a Si content of 0.1wt.%, a Cu content of 0.05wt.%, a Mn content of 0.05wt.%, and a Zn content of 0.1wt.%. The materials of the first anti-corrosion layer and the second anti-corrosion layer include Cr(NO3)3.9H2O and phosphoric acid in a mass ratio of 100:5. The adhesive in the first adhesive layer is an aromatic polyurethane adhesive and the dry adhesive amount is 4.5g / m 2 The adhesive in the second adhesive layer is a maleic anhydride modified polyolefin resin, and the dry adhesive weight is 2.6g / m 2 .
[0059] The preparation method of the aluminum-plastic film of this comparative example may include the following steps.
[0060] (1) Coat the anti-corrosion liquid corresponding to the first anti-corrosion layer and the second anti-corrosion layer on both sides of the aluminum foil, and then dry at 100°C for 3 hours.
[0061] (2) Coating a first adhesive liquid corresponding to the first adhesive layer on the first anti-corrosion layer and coating a second adhesive liquid corresponding to the second adhesive layer on the second anti-corrosion layer.
[0062] (3) A PA layer was laminated on the first adhesive and a CPP layer was laminated on the second adhesive, and then aged at 70°C for 5 days.
[0063] Comparative Example 3 This comparative example is an aluminum-plastic film including a PA layer, a first adhesive layer, a first anti-corrosion layer, an aluminum foil, a second anti-corrosion layer, a second adhesive layer, and a CPP layer stacked in sequence. The raw materials of the aluminum foil have an Al content of 99.5wt.%, an Fe content of 0.2wt.%, a Si content of 0.1wt.%, a Cu content of 0.05wt.%, a Mn content of 0.05wt.%, and a Zn content of 0.1wt.%. The materials of the first anti-corrosion layer and the second anti-corrosion layer are JT-320 Dacromet anti-corrosion coating (with zinc powder, aluminum powder, chromic acid, and deionized water as the main components). The adhesive in the first adhesive layer is an aromatic polyurethane adhesive and the dry adhesive weight is 4.5g / m 2 The adhesive in the second adhesive layer is a maleic anhydride modified polyolefin resin, and the dry adhesive weight is 2.6g / m 2 .
[0064] The preparation method of the aluminum-plastic film of this comparative example may include the following steps.
[0065] (1) Coat the anti-corrosion liquid corresponding to the first anti-corrosion layer and the second anti-corrosion layer on both sides of the aluminum foil, and then dry at 100°C for 3 hours.
[0066] (2) Coating a first adhesive liquid corresponding to the first adhesive layer on the first anti-corrosion layer and coating a second adhesive liquid corresponding to the second adhesive layer on the second anti-corrosion layer.
[0067] (3) A PA layer was laminated on the first adhesive and a CPP layer was laminated on the second adhesive, and then aged at 70°C for 5 days.
[0068] Comparative Example 4 This comparative example is an aluminum-plastic film including a PA layer, a first adhesive layer, a first anti-corrosion layer, an aluminum foil, a second anti-corrosion layer, a second adhesive layer and a CPP layer stacked in sequence. The raw materials of the aluminum foil have an Al content of 99.5wt.%, a Fe content of 0.2wt.%, a Si content of 0.1wt.%, a Cu content of 0.05wt.%, a Mn content of 0.05wt.%, and a Zn content of 0.1wt.%. The first anti-corrosion layer and the second anti-corrosion layer are trivalent chromium coatings, and the coating thickness is 0.1±0.05μm. The adhesive in the first adhesive layer is an aromatic polyurethane adhesive and the dry adhesive amount is 4.5g / m 2 The adhesive in the second adhesive layer is a maleic anhydride modified polyolefin resin, and the dry adhesive weight is 2.6g / m 2 .
[0069] The preparation method of the aluminum-plastic film of this comparative example may include the following steps.
[0070] (1) A trivalent chromium coating is electroplated on both sides of the aluminum foil as the first anti-corrosion layer and the second anti-corrosion layer.
[0071] (2) Coating a first adhesive liquid corresponding to the first adhesive layer on the first anti-corrosion layer and coating a second adhesive liquid corresponding to the second adhesive layer on the second anti-corrosion layer.
[0072] (3) A PA layer was laminated on the first adhesive and a CPP layer was laminated on the second adhesive, and then aged at 70°C for 5 days.
[0073] The aluminum-plastic film in Examples 1-2 and Comparative Examples 1-4 was controlled to have a total thickness of 113±2μm, a PA layer thickness of 25±2μm, an aluminum foil layer thickness of 45±2μm, and a CPP layer thickness of 40±2μm. The aluminum-plastic films prepared in Examples 1-2 and Comparative Examples 1-4 were used as packaging bags to encapsulate a wound-type battery cell, with the metal terminals having a thickness of 100μm and a width of 6mm, and the tab glue having a thickness of 80μm and a width of 2mm. During encapsulation, the top seal was made of brass, with a head width of 1.5mm, a tab limit groove width of 8mm, a tab limit groove depth of 102μm for both the upper and lower heads, a lower head limit groove depth of 198μm for both films, a flatness of less than 5μm for the upper and lower heads, a length of 200mm for the upper and lower heads, and a cylinder diameter of Φ40mm for the encapsulation machine. The top seal packaging conditions were: 195°C, 0.35 MPa, 2 seconds. The side seal and secondary side seal (secondary seal) conditions after liquid injection were: 176°C, 0.2 MPa, 2 seconds. The sealing effect and performance test results of each soft-pack secondary battery are shown in Table 1.
[0074] Table 1 Sealing effect and performance test results of various soft-pack secondary batteries
[0075] From the results in Table 1, it can be seen that the aluminum-plastic film prepared by using chromium nitrate, acrylic resin and phosphoric acid as the material of the anti-corrosion layer not only has a high CPP retention rate, strength and bursting pressure, so the sealing performance of the top seal and side seal is better, but also the ohmic resistance is greatly reduced after the anti-corrosion layer is applied, the shell resistance is high, and it has better anti-short-circuit performance.
[0076] In addition, the morphology of the sealed slices of the side seals of the aluminum-plastic films of Example 1 and Comparative Example 1 was observed, as shown in FIG. Figure 2 and Figure 3 As shown, Figure 2 The middle seal is not cracked, not raised, and is in an arc shape. Figure 3 The middle seal is convex and cracked, indicating that the sealing performance of the aluminum-plastic film of Example 1 is better than that of Comparative Example 1.
[0077] In Comparative Example 1, the absence of phosphoric acid prevented the chromium nitrate from reacting with the aluminum foil surface to form a complex, failing to form a uniform, dense protective layer. In Comparative Example 2, the absence of acrylic resin prevented hydrogen bonding with the aluminum foil, weakening the bonding strength. In Comparative Example 3, a conventional anti-corrosion solution composed primarily of zinc powder, aluminum powder, chromic acid, and deionized water failed to form hydrogen bonds with the aluminum foil and failed to form a uniform, dense protective layer. In Comparative Example 4, an electroplated layer was used as the anti-corrosion layer, failing to form hydrogen bonds with the aluminum foil and failing to form a uniform, dense protective layer.
[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to the embodiments. Those skilled in the art should understand that the technical solutions of the present invention can be applied to The scheme can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. An aluminum-plastic film, characterized in that: The invention comprises a PA layer, a first adhesive layer, a first anti-corrosion layer, an aluminum foil, a second anti-corrosion layer, a second adhesive layer and a CPP layer stacked in sequence. The ohmic internal resistance of the raw material of the aluminum foil is Ω1, the ohmic internal resistance of the aluminum foil after stacking the first anti-corrosion layer and the second anti-corrosion layer is Ω2, and the ohmic internal resistance of the aluminum foil after stacking the first adhesive layer and the second adhesive layer is Ω3. Ω1 / Ω2 is 5-10, and Ω3 ≥ 9000MΩ. The materials of the first anti-corrosion layer and the second anti-corrosion layer include chromium nitrate, acrylic resin and phosphoric acid.
2. The aluminum-plastic film according to claim 1, characterized in that Ω1 is 30~40MΩ, and Ω2 is ≤5MΩ.
3. The aluminum-plastic film according to claim 1, characterized in that The mass ratio of the chromium nitrate, the acrylic resin and the phosphoric acid is 100:40-60:1-10.
4. The aluminum-plastic film according to claim 3, characterized in that The chromium nitrate is Cr(NO3)3.9H2O, the acrylic resin is a water-based acrylic resin, the number average molecular weight of the acrylic resin is 20,000-40,000, and the phosphoric acid is analytically pure H3PO4.
5. The aluminum-plastic film according to claim 1, characterized in that The adhesive in the first adhesive layer is a polyurethane adhesive and the dry adhesive weight is 4.0-5.0 g / m 2 The adhesive in the second adhesive layer is a modified polyolefin adhesive and the dry adhesive amount is 2.2~2.8g / m 2 .
6. The aluminum-plastic film according to claim 5, characterized in that The polyurethane adhesive includes at least one of polyether polyurethane, polyester polyurethane, aromatic polyurethane and aliphatic polyurethane, and the modified polyolefin adhesive includes at least one of maleic anhydride modified polyolefin and acrylic acid modified polyolefin.
7. The aluminum-plastic film according to claim 1, characterized in that The raw materials of the aluminum foil have an Al content of ≥99.2 wt.%, an Fe content of ≤0.3 wt.%, a Si content of ≤0.15 wt.%, a Cu content of ≤0.055 wt.%, a Mn content of ≤0.05 wt.%, and a Zn content of ≤0.1 wt.%.
8. The method for preparing the aluminum-plastic film according to any one of claims 1 to 7, wherein: Including steps: (1) coating the anti-corrosion liquid corresponding to the first anti-corrosion layer and the second anti-corrosion layer on both sides of the aluminum foil respectively, and then drying; (2) coating the first adhesive liquid corresponding to the first adhesive layer on the first anti-corrosion layer and coating the second adhesive liquid corresponding to the second adhesive layer on the second anti-corrosion layer; (3) A PA layer is laminated on the first adhesive liquid and a CPP layer is laminated on the second adhesive liquid, and then aged.
9. A soft-pack secondary battery, comprising a packaging bag and a battery cell contained in the packaging bag, wherein the battery cell comprises a core body and a metal terminal, wherein the metal terminal is connected to the core body and protrudes from the core body, wherein: The packaging bag is the aluminum-plastic film according to any one of claims 1 to 7 or the aluminum-plastic film prepared by the method for preparing the aluminum-plastic film according to claim 8, and the metal terminal includes a connecting portion, a contact portion and an extending portion connected in sequence, the connecting portion is connected to the core body, the contact portion contacts the aluminum-plastic film, and the extending portion extends out of the packaging bag.
10. The soft-pack secondary battery according to claim 9, characterized in that: The aluminum-plastic film in the soft-pack secondary battery has a CPP retention rate of 50% to 80%, the strength of the area where the aluminum-plastic film contacts the contact portion is ≥2N / 6mm, the strength of the area where the aluminum-plastic film does not contact the contact portion is ≥55N / 15mm, the bursting pressure of the aluminum-plastic film in the soft-pack secondary battery is ≥1.0Mpa, and the shell resistance of the aluminum-plastic film in the soft-pack secondary battery is ≥200MΩ.